Flexibility oriented adaptive modeling of combined heat and power plant under various heat-power coupling conditions. (1st March 2022) - Hou, Guolian; Gong, Linjuan; Hu, Bo; Huang, Ting; Su, Huilin; Huang, Congzhi; Zhou, Guiping; Wang, Shunjiang
Abstract: The flexible operation of thermal power plant has become a research hotspot for its safety and validity in eliminating power grid fluctuation from large-scale integration of renewable energy. Heat-power decoupling is effective technique to promote flexibility of combined heat and power plant. To address the insufficient dynamics investigation of combined heat and power plant under different heat-power decoupling strategies, an adaptive modeling approach is proposed. This method systematically fuses the mechanism analysis and data-driven fuzzy modeling to prepare for the controller design for rapid and deep load regulation in flexible operation. Firstly, the model structures with unknown parameters are determined by mechanism analyses to reflect the effects of various decoupling techniques on the characteristics of plant. Secondly, in view of the on-site data under wide load operation conditions, corresponding model structure is adaptively matched, and a new Takagi–Sugeno fuzzy modeling scheme depend on biquantum pigeon optimization algorithm is constructed for model parameters acquisition. The effectiveness of the proposed approach is illustrated based on a 350 MW supercritical combined heat and power unit. Simulation results illustrate that the adopted method can rapidly characterize dynamics of plant under different heat-power coupling conditions. All the model identification and verification errors in wide load operation conditions are less than 3.1% plant output, which reveals high modeling precision more than 97%. Thus, the established model provides solid foundation on highly matched controller for ensuring operational flexibility. Highlights: A modeling approach fusing mechanism analysis and T-S fuzzy modeling is constructed. Various heat-power decoupling technics are considered in modeling of CHP plant. Biquantum pigeon optimization algorithm is proposed for parameter identification. Model effectiveness under two different heat-power coupling conditions is verified.